Regulation of the Wnt signaling pathway during myogenesis by the mammalian SWI/SNF ATPase BRG1 - Sharma, Tapan; Olea-Flores, Monserrat; Imbalzano, Anthony N. (Frontiers in Cell and Developmental Biology, 2023)
Skeletal muscle differentiation is a tightly regulated process, and the importance of the mammalian SWI/SNF (mSWI/SNF) chromatin remodeling family for regulation of genes involved in skeletal myogenesis is well-established. Our prior work showed that bromodomains of mSWI/SNF ATPases BRG1 and BRM contribute to myogenesis by facilitating the binding of mSWI/SNF enzymes to regulatory regions of myogenic and other target genes. Here, we report that pathway analyses of differentially expressed genes from that study identified an additional role for mSWI/SNF enzymes via the regulation of the Wnt signaling pathway. The Wnt pathway has been previously shown to be important for skeletal muscle development. To investigate the importance of mSWI/SNF enzymes for the regulation of the Wnt pathway, individual and dual knockdowns were performed for BRG1 and BRM followed by RNA-sequencing. The results show that BRG1, but not BRM, is a regulator of Wnt pathway components and downstream genes. Reactivation of Wnt pathway by stabilization of β-catenin could rescue the defect in myogenic gene expression and differentiation due to BRG1 knockdown or bromodomain inhibition using a specific small molecule inhibitor, PFI-3. These results demonstrate that BRG1 is required upstream of β-catenin function. Chromatin immunoprecipitation of BRG1, BRM and β-catenin at promoters of Wnt pathway component genes showed binding of BRG1 and β-catenin, which provides further mechanistic insight to the transcriptional regulation of these genes.